Declining Postoperative 90-Day Opioid Prescriptions From 2010 to 2021 Following Hip Arthroscopy for Femoroacetabular Impingement Syndrome - Wesley Day, B.S.; Scott Halperin, B.S.; Serkan Surucu, M.D.; Andrew E. Jimenez, M.D.; Beatrice Katsnelson, B.S.; Justin Zhu, B.S.; Jonathan N. Grauer, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To analyze postoperative opioid prescriptions after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) in a large, opioid-naive population and to evaluate factors associated with receiving more opioids. Methods: Opioid-naive adult patients who underwent hip arthroscopy for FAIS were queried in the 2010 to 2022 PearlDiver Mariner 161 national administrative database. Exclusion criteria included patients with a history of chronic pain and patients who received opioid prescriptions more than 30 days before surgery. Patient variables were extracted: age, sex, and Elixhauser Comorbidity Index. Ninety-day postoperative opioid prescriptions (by total morphine milligram equivalents [MMEs]) were assessed with multivariate linear regression. Ninety-day postoperative opioid prescriptions from 2011 to 2021 were assessed. Results: Of 27,079 patients with postoperative opioid prescriptions identified, a mean ± standard deviation of 347.6 ± 729.2 MMEs (40 tablets of 5 mg oxycodone) were prescribed per patient, with a mean of 1.6 prescriptions filled per patient within 90 days following surgery. Seventy-five percent of patients filled fewer than 600 MMEs, but a small subset filled more than 2,000 MMEs. Multivariate analysis revealed that, compared to patients in the age 30- to 39-year group, those aged 20 to 29 years received fewer MMEs (Δ = –72.5, P < .017). Compared to those with an Elixhauser Comorbidity Index of 2 or under, those >2 were prescribed more MMEs (Δ = 52.5, P < .017). Sex did not correlate with the postoperative MMEs prescribed. From 2011 to 2021, a 58.2% decrease in the 90-day mean MMEs prescribed was noted per patient (P < .017). Conclusions: Fewer postoperative MMEs were filled following FAIS hip arthroscopy for patients in their 20s relative to those in their 30s, as well as for those with lower comorbidity burden. Patient sex was not associated with differences in postoperative MMEs prescribed. The amount of mean MMEs prescribed per patient decreased from 2011 to 2021. Clinical Relevance: This study provides information about the typical amount of narcotics required after surgery. This is increasingly useful information, as surgeons/clinicians continue to try to minimize the role of narcotics in postoperative recovery.